MICRO, MACRO, MONETARY, AND FISCAL SECTORS OF INDONESIAN ECONOMICS DEPEND ON DEFENSE ECONOMICS - Ratih Rachma Kurnia; Prayogi Aprilianto; Haetami Haetami; Lukman Yudho Prakoso; Budi Pramono; Agus Winarna; Yudi Sutrasna; Guntur Eko Saputro; Juliana Juliana; Gabriel Choirul Alman; Gazali Salim; Mursidi Mursidi (Jurnal Cakrawala Ilmiah, 2022)
Indonesia as a developing country, has good awareness of the importance of national development in many aspects. The national development process includes the developments of micro, macro, monetary and fiscal sectors. These factors have affected the allocation of resources, distribution of income, economic growth, and stabilization related to military defense. This paper aims to describe the Indonesian economic condition in 2022 from the defense economics perspective. The method used in this paper is a qualitative literature study with a descriptive and narrative approach. The conclusion is that the Indonesian economic current condition from the micro and macro sectors shows a good development. Furthermore, the policies taken by the government in the monetary and fiscal sectors are considered to be able to stimulate economic recovery. From the defense economics point of view, this condition must be accompanied by conducive country security so the public welfare can be stable